An Experimental Study of the Possibility of In Situ Hydrogen Generation within Gas Reservoirs - Pavel Afanasev; Evgeny Popov; Alexey Cheremisin; Roman Berenblyum; Evgeny Mikitin; Eduard Sorokin; Alexey Borisenko; Viktor Darishchev; Konstantin Shchekoldin; Olga Slavkina (Energies, 2021)
Hydrogen can be generated in situ within reservoirs containing hydrocarbons through chemical reactions. This technology could be a possible solution for low-emission hydrogen production due to of simultaneous CO2 storage. In gas fields, it is possible to carry out the catalytic methane conversion (CMC) if sufficient amounts of steam, catalyst, and heat are ensured in the reservoir. There is no confirmation of the CMC’s feasibility at relatively low temperatures in the presence of core (reservoir rock) material. This study introduces the experimental results of the first part of the research on in situ hydrogen generation in the Promyslovskoye gas field. A set of static experiments in the autoclave reactor were performed to study the possibility of hydrogen generation under reservoir conditions. It was shown that CMC can be realized in the presence of core and ex situ prepared Ni-based catalyst, under high pressure up to 207 atm, but at temperatures not lower than 450 °C. It can be concluded that the crushed core model improves the catalytic effect but releases carbon dioxide and light hydrocarbons, which interfere with the hydrogen generation. The maximum methane conversion rate to hydrogen achieved at 450 °C is 5.8%.